Computer literacy and attitudes towards information & communication technology (ICT): A survey among health professionals at Hospital Selayang / Abdul Hafeez Ahmad Hamdi - Ahmad Hamdi, Abdul Hafeez (2008)
To use technology effectively for the advancement of patient care, health care professionals must possess a variety of computer skills. Hospital Selayang was one of the hospital which using Total Hospital Information System (THIS). This project aimed to assess the computer literacy level and basic computer skills among health professionals (doctors, pharmacists, nurses, and assistant Pharmacists) at Hospital Selayang. Sixty five self administered questions were distributed during the Continuous Medical Education (CME) sessions at Hospital Selayang. Over 300 questionnaires were distributed, 25 I questionnaires were answered giving the response rate of 83.6%. The survey responses reflected the opinions of health professional at Hospital Selayang with different department, educational background, and working experienced. Majority (205 ,86.1 %) of respondents have used a computer prior to joining the hospital (p< .05), and 200 (84 %) of respondents have a computer at their home (p< .05). Respondents working status and age significantly influenced computing knowledge. Generally health care professionals reported favorable attitude toward ICT where 230 (97%) agreed that they intend to use IT in their further practice (p< .05). It can be conclude that most of the health professionals at Hospital Selayang meet the minimum information technology competencies necessary to perform their work efficiently however medical databases skills and internet surfing skills were identified as those in greatest need of improvement. Strategies to enhance computer skills among health professionals also have been proposed.